FISHING IN THE LARGEST PERENE HYPERSALINE LAGOON IN SOUTH AMERICA, WITH NOTES ON CURRENT REGULATIONS - Márcio Luís Chagas MACEDO; Sérgio Ricardo SANTOS; Maurício Düppré de ABREU; Hugo ZECCHIM; Karina Annes KEUNECKE; Geraldo TIMOTEO; Marcelo VIANNA (Boletim do Instituto de Pesca)
Araruama Lagoon (Rio de Janeiro) is the largest hypersaline lagoon in South America. The aim of this study was to survey fishing landings, capture areas and production at this lagoon, in addition to analyzing data from the Pescarte Census. Fishing landings were monitored daily by community agents from March to August/2009, through the Petrobras Mosaico Program. Thirteen landing points were identified in five municipalities, totaling 8,096 recorded landings, and accumulating 469.1 tonnes. São Pedro da Aldeia (39.6%), Arraial do Cabo (27.7%) and areas in the central region (37.6%) and the south coast (29.1%) of the lagoon presented the highest landings and catch volumes. Twelve species were identified, mainly Pogonias courbina (48.9%) and Penaeus spp (33.8%), and gillnets were the most important fishing gear. Very few studies have addressed fishing at Araruama Lagoon, leading to current planning measures supported by little data. We advocate a participatory review of current regulations, to better address gillnet fishing and the capture of different fish species. This study is the result of research financed by the Pescarte Environmental Education Project, a mitigation measure required by the Federal Environmental Licensing, conducted by IBAMA.